Evaluasi Struktur menggunakan variasi tipe pelat lantai menggunakan evaluasi kapasitas: Studi kasus area kerja yang umum dipergunakan di Surabaya - Dewi Pertiwi; Indra Komara; Yanisfa Septiarsilia; Dita Kamarul Fitriah (LPPM Universitas Negeri Jakarta, 2023)
Improvement of the current construction of midrise to high-rise building in Surabaya relatively needs to be evaluated, especially for compact office building area, it is very challenging to have an optimal space to the structural system with facilitate a satisfactory capacity performance. This paper makes a comparative study of the effectivity of structural plate structure in the compact office building between conventional slab (M1), waffle slab (M2) and flat slab (M3). A typical 5-story reinforced concrete building structure is selected as a case study within 6 m symmetrically span for each model. The proposed method used in this study is based on empirical analysis followed by numerical evaluation using SAP2000. The step initiated by deriving an optimal alternative of various type of slab. This study aims to emphasize the benefits to the functionality of the structural system which more efficient in term of structural capacity and its performance. As the result, M1 and M3 offer a similar behaviour due to the reinforcement and design performance with high slab deformation compared to the M2. M2 present a lower slab deflection under the supported of waffle element with the result almost twice smaller than M1 and M3.